Factors of Formation of the Secondary School Children Status Among Classmates - НазарбаеваЕлена Алексеевна (Journal of Economic Sociology, 2011)
The paper presents an attempt to describe how status among classmates is attained at the secondary school. Exchange theory perspective is applied. Making it similar to stratification research, the author reveals key factors of status attainment including educational scores and use of pocket money. Using survey data collected from the seventh-grade pupils at a Moscow suburbs secondary school, the author draw some conclusions on potential connections between a child’s status and his/her inclinations to help classmates to study, as well as an impact of the pocket money usage and formal power.